THE EFFECT OF TAX INCENTIVE AND TAX SERVICES DIGITALIZATION ON TAXPAYER COMPLIANCE DURING THE COVID-19 PANDEMIC WITH THE MODERATING ROLE OF SOCIALIZATION - Juita Tanjung (International Journal of Economics, Business, and Entrepreneurship, 2023)
This study aims to explore the effect of tax incentive and tax services digitalization on taxpayer compliance during the COVID-19 pandemic with the moderating role of socialization. This study employs quantitative method with primary data obtained from questionnaires. The population of this study is individual taxpayers registered at the Tax Office of Indramayu, and with random sampling, we obtained 100 respondents as our samples. We analyzed the data using the Moderated Regression Analysis. The results of this study indicate that tax incentive does not have a significant positive effect on taxpayer compliance, while the tax services digitization has a positive and significant effect on taxpayer compliance. Furthermore, socialization has an insignificant negative effect in moderating the relationship between tax incentive on taxpayer compliance and socialization has no positive effect in moderating the relationship between tax services digitization and individual taxpayer compliance. Keywords: Individual Taxpayer Compliance, Tax Incentive, Tax Services Digitalization and Socialization.